2015
DOI: 10.1016/j.ijosm.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of osteopathic manipulative treatment on length of stay in posterolateral postthoracotomy patients: A retrospective case note study

Abstract: Objective: This study retrospectively evaluated the effect of OMT on length of stay (LOS) in hospitalized posterolateral postthoracotomy patients. Methods: Inpatient medical records of patients who received posterolateral thoracotomies with lung resection between 1998 and 2011 were reviewed for demographic data, LOS, thoracotomy surgery data, consultation data excluding osteopathic manipulative medicine, discharge data, and osteopathic manipulative medicine consultation data. Results: Thirty-eight patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Postoperative LOS was measured in a majority of the included studies. 18 20 , 23 , 25 , 26 The results from 2 articles suggest shorter LOS due to complementary surgical care with OMT. 18 , 19 Baltazar et al 18 found that general surgical patients given OMT (n = 17) had a significantly ( P = .006) shorter LOS compared to general surgical patients not receiving OMT (n = 38), of approximately 5 days in mean.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Postoperative LOS was measured in a majority of the included studies. 18 20 , 23 , 25 , 26 The results from 2 articles suggest shorter LOS due to complementary surgical care with OMT. 18 , 19 Baltazar et al 18 found that general surgical patients given OMT (n = 17) had a significantly ( P = .006) shorter LOS compared to general surgical patients not receiving OMT (n = 38), of approximately 5 days in mean.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative bowel function as a measure of OMT effects was presented in 4 studies. 18 , 20 , 25 , 26 Among general surgical patients, Baltazar et al 18 found a significantly ( P = .035) shorter time to first postoperative flatus in the OMT provided group (n = 17) compared to the non-OMT provided group (n = 38) by approximately 1.5 days in mean, and no statistical differences between the groups in time for first postoperative bowel movement ( P = .43) or start of postoperative clear liquid diet ( P = .59). Post-thoracotomy, Fleming et al 20 found no difference in postoperative ileus incidence between the OMT group (n = 23) and the non-OMT group (n = 15).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations